Motivation and Use of Social Media to Increase Student Entrepreneurial Interest - Hugo Aries Suprapto (International Journal of Integrative Research, 2023)
This study aims to find out the learning of entrepreneurship in shaping the potential interest in entrepreneurship in students. This research is a qualitative research using a qualitative descriptive method. The data collection used is by observing, interviewing, and documentation. While in analyzing the data, the researcher uses descriptive qualitative analysis techniques. While checking or checking the validity of the data using triangulation techniques. The sample in this study were 3 classes in odd semester 2019/2020 students. Based on the results of the researchers' initial observations with several students in 3 classes of Industrial Engineering Study Program, Indraprasta University PGRI Jakarta, information was obtained that they said they had not been able to apply the Entrepreneurial Spirit in everyday life. The results of the evaluation carried out at the beginning during the research in the learning process in class, the theoretical learning method alone still does not attract students' interest in learning so that they become interested in addition to the theory of applying entrepreneurial application learning methods in the practice of making products. The results of the study show that entrepreneurship learning is carried out in addition to theory, namely the practical application of how to make a product by involving students.